Academic domains as political battlegrounds: A global enquiry by 99 academics in the fields of education and technology - Al Lily, A.; Foland, J.; Stoloff, D.; Gogus, A.; Deniz Erguvan, I.; Tomé Awshar, M.; Tondeur, J.; Hammond, M.; Venter, I.; Jerry, P.; Vlachopoulos, D.; Oni, A.; et al. (2017)
This article theorizes the functional relationship between the human components (i.e., scholars) and non-human components (i.e., structural configurations) of academic domains. It is organized around the following question: in what ways have scholars formed and been formed by the structural configurations of their academic domain? The article uses as a case study the academic domain of education and technology to examine this question. Its authorship approach is innovative, with a worldwide collection of academics (99 authors) collaborating to address the proposed question based on their reflections on daily social and academic practices. This collaboration followed a three-round process of contributions via email. Analysis of these scholars’ reflective accounts was carried out, and a theoretical proposition was established from this analysis. The proposition is of a mutual (yet not necessarily balanced) power (and therefore political) relationship between the human and non-human constituents of an academic realm, with the two shaping one another. One implication of this proposition is that these non-human elements exist as political ‘actors’, just like their human counterparts, having ‘agency’ – which they exercise over humans. This turns academic domains into political (functional or dysfunctional) ‘battlefields’ wherein both humans and non-humans engage in political activities and actions that form the identity of the academic domain. For more information about the authorship approach, please see Al Lily AEA (2015) A crowd-authoring project on the scholarship of educational technology. Information Development. doi: 10.1177/0266666915622044.